Antifungal and antibiofilm effects of probiotic Lactobacillus salivarius, zinc nanoparticles, and zinc nanocomposites against Candida albicans from Nile tilapia (Oreochromis niloticus), water and humans - El-Gazzar, Nashwa; Elez, Rasha M. M. Abou; Attia, Amira S. A.; Abdel-Warith, Abdel-Wahab A.; Darwish, Manal M.; Younis, Elsayed M.; Eltahlawi, Rehab A.; Mohamed, Kawthar Ibraheem; Davies, Simon J.; Elsohaby, Ibrahim (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Candida albicans (C. albicans) can form biofilms; a critical virulence factor that provides effective protection from commercial antifungals and contributes to public health issues. The development of new antifungal therapies, particularly those targeting biofilms, is imperative. Thus, this study was conducted to investigate the antifungal and antibiofilm effects of Lactobacillus salivarius (L. salivarius), zinc nanoparticles (ZnNPs) and nanocomposites (ZnNCs) on C. albicans isolates from Nile tilapia, fish wash water and human fish sellers in Sharkia Governorate, Egypt. Methods: A cross-sectional study collected 300 samples from tilapia, fish wash water, and fish sellers (100 each). Probiotic L. salivarius was immobilized with ZnNPs to synthesize ZnNCs. The study assessed the antifungal and antibiofilm activities of ZnNPs, L. salivarius, and ZnNCs compared to amphotericin (AMB). Results: Candida spp. were detected in 38 samples, which included C. albicans (42.1%), C. glabrata (26.3%), C. krusei (21.1%), and C. parapsilosis (10.5%). A total of 62.5% of the isolates were resistant to at least one antifungal agent, with the highest resistance to nystatin (62.5%). However, 75% of the isolates were highly susceptible to AMB. All C. albicans isolates exhibited biofilm-forming capabilities, with 4 (25%) isolates showing strong biofilm formation. At least one virulence-associated gene (RAS1, HWP1, ALS3, or SAP4) was identified among the C. albicans isolates. Probiotics L. salivarius, ZnNPs, and ZnNCs displayed antibiofilm and antifungal effects against C. albicans, with ZnNCs showing significantly higher inhibitory activity. ZnNCs, with a minimum inhibitory concentration (MIC) of 10 µg/mL, completely reduced C. albicans biofilm gene expression. Additionally, scanning electron microscopy images of C. albicans biofilms treated with ZnNCs revealed asymmetric, wrinkled surfaces, cell deformations, and reduced cell numbers. Conclusion: This study identified virulent, resistant C. albicans isolates with strong biofilm-forming abilities in tilapia, water, and humans, that pose significant risks to public health and food safety.